High-throughput sequencing reveals no viral pathogens in eight cases of ocular adnexal extranodal marginal zone B-cell lymphoma. (August 2019) - Mollerup, Sarah; Mikkelsen, Lauge Hjorth; Hansen, Anders Johannes; Heegaard, Steffen
Abstract: The purpose of the present study was to perform a next-generation sequencing (NGS) based analysis of viruses in ocular adnexal extranodal marginal zone B-cell lymphoma (EMZL). Eight patients with extraocular EMZL were identified in the archives of Department of Ophthalmology, Copenhagen University Hospital. All cases were validated according to the World Health Organization classification. We subjected samples to enrichment of virion-associated (encapsidated) nucleic acids which included sample homogenization, filtration, and nuclease treatment. Both DNA and RNA were sequenced, and we analyzed the sequencing data for the presence of viral sequences. We detected no pathogenic viruses likely to be associated to development of EMZL. In one case, we detected human polyomavirus 7 and traces of Epstein-Barr virus (EBV) (human herpesvirus 4 (HHV4)) and a human papillomavirus. In conclusion, no viral pathogens were consistently detected in the extraocular EMZL samples when applying NGS-based methods. Highlights: 8 samples of ocular adnexal extranodal marginal zone B-cell lymphoma were investigated. Advanced microbial enrichment was performed in order to identify known and unknown viral pathogens. Next-generation sequencing detected neither DNA virus nor RNA virus in ocular adnexal EMZL.